Cracking the new GRE, with DVD - Pierce, Douglas (Random House, 2011)
Presents a guide to assist with preparation for the new GRE, with practice questions pertaining to the verbal, math, and analytical writing sections; tips, techniques, and detailed explanations for answers; and access to four full-length practice tests.